Condicionantes de producción que influyen en las rutinas de realización de revista SKP (2016)
The field of publishing of magazines is undoubtedly an amalgam of disciplines coming together in a single medium, among these, art, design, journalism, advertising and literature, which varied research raises concerns that can raise from preproduction, production, circulation and consumption of the media. For the development of this study, academic-practice reflection will be part of the conditions of internal and external production SKP magazine and how they influence the performance of the same. This research aims to show how they influence in these conditions in CPC Agency, primarily in the information content and in every activity produced by the practitioner and the collaborating organization.